2019
DOI: 10.3389/fcimb.2019.00416
|View full text |Cite
|
Sign up to set email alerts
|

PCR-Based Detection of Cryptosporidium spp. and Enterocytozoon bieneusi in Farm-Raised and Free-Ranging Geese (Anser anser f. domestica) From Hainan Province of China: Natural Infection Rate and the Species or Genotype Distribution

Abstract: Cryptosporidium spp. and Enterocytozoon bieneusi are two important zoonotic pathogens that can infect humans and a broad range of animal hosts. However, few studies have been conducted to study infection of the two pathogens in domestic geese until now. The aims of the present study were to determine the prevalence of natural infection, and the species or genotype distribution of Cryptosporidium and E. bieneusi in farm-raised and free-ranging geese from Hainan Province of China. In total, 266 fecal samples of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…C. baileyi, originally isolated from commercial broiler chickens [29], has a broad range of avian hosts and is considered the predominant avian Cryptosporidium species. In China, C. baileyi has been reported in a wide variety of birds, including chickens, quails, ostriches, Pekin ducks, domestic pigeons, geese, as well as some pet birds [4,6,9,16,28,30]. Evidence has shown that C. baileyi causes respiratory disease and production loss in chickens, causing reduced weight gain in broilers and decreased egg production in layer chickens [31].…”
Section: Discussionmentioning
confidence: 99%
“…C. baileyi, originally isolated from commercial broiler chickens [29], has a broad range of avian hosts and is considered the predominant avian Cryptosporidium species. In China, C. baileyi has been reported in a wide variety of birds, including chickens, quails, ostriches, Pekin ducks, domestic pigeons, geese, as well as some pet birds [4,6,9,16,28,30]. Evidence has shown that C. baileyi causes respiratory disease and production loss in chickens, causing reduced weight gain in broilers and decreased egg production in layer chickens [31].…”
Section: Discussionmentioning
confidence: 99%
“…55, No. 1 (2024) SHADAN H. ABDULLAH in geese, a lower prevalence of cryptosporidiosis than current finding 4.1% was reported by Zhao et al [38], and a high prevalence of 44.7% was reported by Binkley et al [39].…”
Section: Higher Prevalence Of Cryptosporidiosis 37%mentioning
confidence: 65%
“…In other study, C. parvum was the predominant species and was identified in broilers, laying chickens and turkeys [33]. According to the finding of Zhao et al [38] the main reported species in geese was C. baileyi, also Nakamura and Meireles [14] was identified C. baileyi from ducks and geese, while other studies have specified the role of geese as possible vectors for C. parvum [42].…”
Section: Higher Prevalence Of Cryptosporidiosis 37%mentioning
confidence: 96%
“…Cryptosporidium baileyi , originally isolated from commercial broiler chickens [ 34 ], has a broad range of avian hosts and is considered the predominant avian Cryptosporidium species. In China, C. baileyi has been reported in a wide variety of birds, including chickens, quails, ostriches, Pekin ducks, domestic pigeons and geese, as well as some pet birds [ 3 , 5 , 8 , 23 , 33 , 35 ]. Recently, C. baileyi was also found in an immunocompetent woman with a benign tumor in Poland [ 22 ].…”
Section: Discussionmentioning
confidence: 99%